PERANAN SYEIKH ABDURRAHMAN YA’QOEB SEBAGAI TOKOH PENDIDIKAN ISLAM DI KABUPATEN INDRAGIRI HILIR (1938-1961) - Sumarni, Titin; Kamaruddin, Kamaruddin; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Sheikh Abdurrahman Ya'qoeb with his first name is Mansur Rajab he is a scholar who persistently strives to develop Islamic education in Indragiri Hilir. In order to fulfill his desire to deepen the science of religion he also studied in the holy land of Mecca for 11 years, besides studying he also won the trust to teach at school Darul Ulumu Al-Diniyah for 5 years. In 1938 he arrived in Indragiri downstream and settled in the bay in a sapat, this is the beginning of his journey in advancing Islamic religious education many things he did to realize these ideals among which he built several educational institutions and build some infrastructure so that he known as the pioneer of the founding of madrassas in Indragiri Hilir. The purpose of this research is to know the life of Sheikh Abdurrahman Ya'qoeb, the role of Sheikh Abdurrahman Ya'qoeb in the field of Islamic educational institution development, the teaching method used by Sheikh Abdurrahman Ya'qoeb, the role of Sheikh Abdurrahman Ya'qoeb in the field of infrastructure development in Keritang Sub-district, the works of Sheikh Abdurrahman Ya'qoeb in papers and art. The method used is qualitative, this research is field research to obtain data through interview and documentation. The result of this research is that Sheikh Abdurrahman Yaqoeb was born in Bangkar Village of Reteh Sub-district on October 12, 1912 and died on October 6, 1970, during his lifetime he spent his time developing Islamic religious education in Indragiri Hilir Regency by establishing several educational institutions such as madrasa and mosque. Sheikh abdurrahman Ya'qoeb also plays a role in building infrastructure such as roads and markets in Keritang sub-district such as Pasar Kembang and Gergaji Village, besides that he is also a productive scholar who has written many works in the field of religion and he is also rich in art such as creating some songs are Islamic nuances.Keywords: Sheikh Abdurrahman Ya'qoeb, role, Indragiri Hilir